(untitled) (American Journal of Pedagogical and Educational Research, 2024)
The formation of pedagogical communication plays an important role in the professional competence of teachers in mother tongue classes. The level of readiness of the dialogue participants for this process depends on the formation of certain necessary skills during education. It is known that many methods of theoretical and practical language acquisition were used in the early stages of the development of the language teaching methodology. However, today there is a growing demand for language learning based on need. The article talks about professional communication competence, its types, methods of developing monologic and dialogic forms of professional speech.